Free vibrations of laminate plates with viscoelastic layers using the refined zig-zag theory – Part 2. Numerical analysis. (15th December 2021) - Litewka, Przemysław; Lewandowski, Roman; Wielentejczyk, Przemysław
Highlights: Efficient solution procedure for non-linear eigen-value problem based on homotopy and quasi-Newton methods. Numerical verification of the proposed formulation and testing of various solution variants. Extensive analyses of results sensitivity to the model parameters. Abstract: In this paper the numerical procedure to solve the non-linear eigen-value problem describing the free vibrations of the laminate plates with viscoelastic (VE) layers is presented. The derivation of that main equation based on the refined zig-zag theory and using fractional Zener material model to describe VE material is presented in the companion paper Lewandowski R, Litewka P. Wielentejczyk P. Free vibrations of laminate plates with viscoelastic layers using the refined zig-zag theory – Part 1. Theoretical background . The solution obtained using the continuation method provides the required dynamic characteristics of the plates – the frequency and the damping ratio. In the iterative part of each continuation step either the full Newton or the quasi-Newton iterative procedure are used. Several numerical examples are solved to verify accuracy, efficiency and versatility of the proposed formulation. Numerous parametric studies are carried out to determine the influence of various solution variants and combinations of material parameters onto the results describing the damping properties of laminate plates.